A delayed diagnosis of cardiac tamponade. (10th April 2013) - McGinley, Abigail; Gribbin, Guy
Abstract : A 64-year-old female was referred to the on-call surgical team by her general practitioner with a 2-week history of feeling generally unwell; more short of breath with lethargy and myalgia with a 2-day history of right upper quadrant abdominal pain. On initial assessment she was tachycardic and an abdominal examination revealed a soft abdomen with right upper quadrant tenderness. An abdominal ultrasound scan revealed a distended gall bladder with the diameter of the common bile duct at the upper limit of normal. It also revealed free fluid within the abdomen, bilateral pleural effusions and a large left ovarian cyst. The medical team became involved and ordered a CT thorax and abdomen which showed a large pericardial effusion, bilateral pleural effusions, a small amount of ascites and a large left ovary; reported as appearances most consistent with malignancy. On further assessment by a cardiologist the patient showed signs of cardiac tamponade and she underwent urgent pericardiocentesis.